The role of higher school in personal becoming - Ponikarovska, Svitlana; Понікаровська, Світлана Володимирівна; Поникаровская, Светлана Владимировна (Харківський національний автомобільно-дорожній університет, 2020)
The article looks into the main principles of students’ social adjustment during their studies at the university and analyzes how this process influences enhancement of their creative activity and shapes their personality. The article emphasizes the necessity for the educational process to accomplish the comprehensive development of the future specialist’s personality.
Роль вищої школи у становленні особистості
Роль высшего образования в становлении личности человека
Keywords: assimilation; social adjustment; individual; communication; interaction; асиміляція; соціальна адаптація; особистість; комунікація; взаємодія; ассимиляция; социальная адаптация; личность; коммуникация; взаимодействие; 378.147; 10.30977/BUL.2219-5548.2020.91.0.216